Design of Mobile 4G Gateway Based on Zigbee Wireless Sensor Network - Qiu, Bo (International Journal of Online and Biomedical Engineering (iJOE), 2018)
To realize the design of mobile 4G gateway of ZigBee wireless sensor network (WSN), a scheme of wireless remote monitoring based on ZigBee and general packet radio service (GPRS) WSN gateway system is proposed. The scheme combines the advantages of short distance, low power consumption, low cost and long distance popular communication of ZigBee technology, and uses the system architecture of ZigBee + GPRS + Android. On this hardware platform, the transplantation of Android system and the development of related hardware device drivers are designed and implemented, so as to build the software platform of the system. Based on the software and hardware platform of the system, the related applications are designed and realized according to the function requirements of the system, and the software and hardware platform and the application program are tested and analyzed. The test results show that the system runs steadily and has good performance. To sum up, the hardware platform has the advantages of low energy consumption, high performance and scalability.